The European Pillar of Social Rights: An Analysis - Daniel Seikel (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2017)
At the Social Summit in Gothenburg, on November 17th, 2017, the European Parliament, the Council and European Commission adopted the "European Pillar of Social Rights" (EPSR). It consists of 20 very generally formulated social policy (in the broadest sense of the word) principles which have been adopted in the form of a legally non-binding joint proclamation. The principles are formulated as social rights of individuals against the member states (Höpner 2017; Rasnaèa 2017, p. 17 onwards). The member states shall comply with these principles and implement them in national legislation. Furthermore, the principles shall be substantiated by legislative initiatives at EU level. The objectives that the Commission pursues with the EPSR are extremely ambitious. The pillar shall serve as a compass for a renewed process of convergence towards better working and living conditions in Europe (Rasnaèa 2017, p.13). Through the EPSR, the Commission is sending the signal that it has recognized the importance of Europe's social dimension. The Commission's initiative has to be seen before the background of the ongoing social problems in Europe, especially in some countries of the Eurozone. This WSI Policy Brief analyses and evaluates the European Pillar of Social Rights with regard to its impact on national and European policies. – – Am 26. April 2017 hat die Europäische Kommission ein Maßnahmenpaket vorgelegt, mit dem sie die soziale Dimension der Europäischen Union stärken will. Der zentrale Bestandteil des Pakets ist eine "Europäische Säule Sozialer Rechte" (ESSR). Diese besteht aus 20 sehr allgemein formulierten, im weitesten Sinn sozialpolitischen Grundsätzen, die in Form einer rechtlich-unverbindlichen gemeinsamen Proklamation von Kommission, Rat und Europäischem Parlament am 17. November 2017 auf dem Sozialgipfel in Göteborg verabschiedet werden soll. Die Prinzipien sind in Form sozialer Rechte von Individuen gegenüber den Mitgliedstaaten formuliert (Höpner 2017; Rasnaèa 2017, S.17f.). Die Mitgliedstaaten sollen die Prinzipien im Rahmen ihrer nationalen Gesetzgebung befolgen und umsetzen. Darüber hinaus sollen die Grundsätze auch durch europäische Gesetzesinitiativen konkretisiert werden. Die Ziele, die die Kommission mit der ESSR verknüpft, sind äußerst ambitioniert. Die Säule soll als Kompass für einen erneuerten Prozess der aufwärts gerichteten Konvergenz hin zu besseren Arbeits- und Lebensbedingungen in Europa dienen (Rasnaèa 2017, S.13). Mit der ESSR signalisiert die Kommission, dass sie die Bedeutung der sozialen Dimension Europas erkannt hat. Hintergrund sind die anhaltenden sozialen Probleme in Europa, insbesondere in einigen Ländern der Eurozone. Der vorliegende WSI Policy Brief analysiert und bewertet die Europäische Säule Sozialer Rechte hinsichtlich ihrer Auswirkungen auf nationale und europäische Politik.
urn:nbn:de:101:1-201802215401; Additional information: This is a translation of a slightly modified version of Seikel, Daniel: “Was bringt die Europäische Säule Sozialer Rechte”, WSI Policy Brief No. 17, 11/2017: http://hdl.handle.net/10419/224224
Keywords: 330